A ANALISIS PENGGUNAAN RELASI MAKNA HIPONIM DAN HIPERNIM PADA ARTIKEL BERITA DIGITAL CNN EDISI OKTOBER 2024 - Asabilah, Fifi; Solikhati, Nur Indah (UIR Press, 2025)
This research is motivated by the existence of hyponyms and hypernyms found in digital news articles from CNN. A hyponym is a word that has a specific or detailed meaning within a particular category, while a hypernym is a word with a general meaning that encompasses several hyponyms. This research aims to analyze the use of hyponym and hypernym meanings in CNN digital news articles from the October 2024 edition, specifically in the lifestyle category, focusing on the health and food sections. This qualitative research employs content analysis methods on selected news articles. Data collection was carried out using observation and note-taking techniques, while data validity was ensured through theoretical triangulation. The results indicate that there are 26 forms of hyponym and hypernym usage in the lifestyle news category, particularly in the health and food sections. An example of a hyponym is found in data excerpt number 25: “Besides purple, there are also eggplants that are green, yellow, and even white,” where the words ‘green,’ ‘yellow,’ and ‘white’ function as hyponyms. Meanwhile, an example of a hypernym is found in data excerpt number 26: “These events feature cultural activities and performances, arts, and cultural activists from the majority populations of Saudi Arabia, as well as representatives from India, the Philippines, Indonesia, Pakistan, Yemen, Sudan, and Jordan.” The word ‘countries’ is a hypernym encompassing these various nations. From these findings, it can be discussed that the use of hyponyms and hypernyms in digital news articles plays an important role in providing clarity and specificity of meaning within the context of lifestyle news, particularly in the health and food sections.